2019
DOI: 10.1519/jsc.0000000000002786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-Week In-Season Elastic Band Training Program on Explosive Muscle Performance, Change of Direction, and Repeated Changes of Direction in the Lower Limbs of Junior Male Handball Players

Abstract: Aloui, G, Hammami, M, Fathloun, M, Hermassi, S, Gaamouri, N, Shephard, RJ, and Chelly, MS. Effects of an 8-week in-season elastic band training program on explosive muscle performance, change of direction, and repeated changes of direction in the lower limbs of junior male handball players. J Strength Cond Res 33(7): 1804–1815, 2019—The aim of this study was to examine the effects of incorporating 8 weeks of biweekly lower-limb elastic band training (knee and hip extension) into the in-season regimen of junior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
53
3
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(87 citation statements)
references
References 32 publications
10
53
3
12
Order By: Relevance
“…In our study muscle volume of the upper limb in players of the first league were relatively more developed than the value of players of the second league. Muscle volume of upper limb First Tunisia Handball League found in the present study was higher than that seen by (Hermassi et al, 2011) of elite handball players, but was similar to those reported by Aloui et al (2018) and Chelly et al (2010a) of male handball players. In fact, the First Tunisia Handball League, pivots (4.06 ± 0.27 l) achieved higher values than backs (4.05 ± 0.96 l) and wings (3.06 ± 0.49 l).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study muscle volume of the upper limb in players of the first league were relatively more developed than the value of players of the second league. Muscle volume of upper limb First Tunisia Handball League found in the present study was higher than that seen by (Hermassi et al, 2011) of elite handball players, but was similar to those reported by Aloui et al (2018) and Chelly et al (2010a) of male handball players. In fact, the First Tunisia Handball League, pivots (4.06 ± 0.27 l) achieved higher values than backs (4.05 ± 0.96 l) and wings (3.06 ± 0.49 l).…”
Section: Discussionsupporting
confidence: 90%
“…The cross-sectional area of the thigh in First Tunisia Handball League players were significantly higher than the second league players but similar to those reported by Hermassi et al (2011) and less than that seen by Aloui et al (2018) in junior's handball players. In fact, the First Tunisia Handball League, the backs (201 ± 2.67 cm 2 ) achieved higher values of thigh muscle than pivots (200 ± 2.41 cm 2 ) and wings (180 ± 6.60 cm 2 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations